Application of physico-chemical and chromatographic techniques for detection of adulteration in ghee (Milk fat) - Shinde, Dnyaneshwar; Darji, Hriday; Chawla, Rajiv; Patel, Badal; Joshi, Chitrangana; Thakkar, Hima; Gawande, Sushil; Patil, Swati; Nair, Rajesh R (Indian Journal of Dairy Science, 2020)
Ghee (milk fat) due to its high price and demand is highly susceptible to adulteration for economic gains. Further, due to advanced practices of adulteration, its detection is becoming difficult by any single method. In the present study, methods based upon physico-chemical (BR reading and RM value) and chromatography (fatty acid, triglycerides, and plant sterols profiling) were evaluated to detect adulteration. Pure ghee was adulterated @ 1%, 2.5%, 5%, and 10% with coconut, soya bean, groundnut, and sunflower oil. Results of physico-chemical methods indicated that BR reading crossed regulatory limit only @ 10% of sunflower and soya bean oil adulteration while for the other two oils it was within the acceptable range (FSSAI standards for Gujarat i.e. 40 to 43.5). In the case of RM value, adulteration was not detected with any oil up to 10% level of adulteration with respect to FSSAI regulation (i.e. minimum 24) for Gujarat. Among chromatographic methods, fatty acids marker molecules like lauric for coconut and linoleic for soya bean, groundnut, and sunflower oil showed an increase upon adulteration even @ 1%. Marker fatty acids % values were falling outside the range for lauric (i.e.2.3 to 3.2%) and linoleic (i.e.1 to 2%) as specified by FSSAI in the manual of analysis for milk and milk products 2016 however, natural variations might affect the results. Triglyceride profiling was found to be capable of detecting adulteration @ 5% for all the oils except groundnut which was detected @ 10%. Plant sterols (â-sitosterol and stigmasterol) based method was found suitable to detect adulteration @ 1% with sunflower and soya bean oil, @ 2.5% with groundnut oil, and @ 5% with coconut oil. All the methods appear to have their strengths and limitations; hence laboratories may apply a combination of techniques to detect advanced adulteration.